2x - 4y + 1z = 11 ⇒ 2x - 4y + 1z = 11
1x + 2y + 3z = 9 ⇒ <u>1x + 2y + 3z = 9</u>
3x + 5z = 12 1x - 2y - 2z = 2
1x - 2y - 2z = 2
2x - 4y + 1z = 11 <u>-2x + 2y - 2z = -3</u>
1x + 2y + 3z = 9 ⇒ 1x + 2y + 3z = 9 x - 4z = 1
3x + 5z = 12 ⇒ <u>3x + 5z = 12</u> x - 4z + 4z = 1 + 4z
-2x + 2y - 2z = -3 x = 1 + 4z
<u /> 1 + 4z - 2y - 2z = 2<u />
1 - 2y + 4z - 2z = 2
1 - 2y + 2z = 2
<u>- 1 - 1</u>
-2y + 2z = 1
-2y + 2z - 2z = 1 - 2z
<u>-2y</u> = <u>1 - 2z</u>
-2 -2
y = -0.5 + z
x + 2(-0.5 + z) - 2z = 2
x - 1 + z - 2z + 2 = 2
x - 1 + z = 2
<u> + 1 + 1</u>
x + z = 3
x - x + z = 3 - x
z = 3 - x
<u />
$2, because if you do 8*25 you get 200 and if you divide that by 100 you get a total of 2 making the tax on the purchase $2.
Answer:
1/4 of 10
Step-by-step explanation:
Answer:
b
Step-by-step explanation:
sequnce 105 865
Answer:
Linear. While all linear equations produce straight lines when graphed, not all linear equations produce linear functions. In order to be a linear function, a graph must be both linear (a straight line) and a function (matching each x-value to only one y-value).